Hungarian endeavours for the enhancement of economic relations in Southeast Asia focusing on a new partnership with Vietnam - Kozár, László; Neszmélyi, György Iván (Applied Studies in Agribusiness and Commerce, 2020)
Beyond a brief review of the economic integration process among the states of the ASEAN region, the authors of the present study aimed to examine and analyze the main economic, social and political characteristics of the Hungaro-ASEAN relations. The importance of the topic of this research is underlined by the fact that the Hungarian government considers big importance to the improvement of the foreign economic relations with Asian economies. This intention was expressed by a new foreign economic strategy „Eastern opening” announced by the government in 2012, even though the foreign trade statistical figures did not justify its success by now.The authors believe that increasing opening towards Asia serves Hungarian economic interests. Therefore, it is a right and desirable direction to proceed, they consider that in the background of the modest results there might be the insufficient knowledge of the market mechanisms, the actors of the local supply chains and the potential partners. They believe that in order to make the Hungarian foreign economic endeavours in this direction more successful a more thorough examination of the local characteristics – including the actual demand arising at the targeted markets - is necessary. This opinion is prevalent to not only the Asian „Giants”, like China, India and Japan, but also to smaller states, like the ASEAN members, which – together - in terms of population and economic performance – reach the dimensions of an economic great power as well. Furthermore, the integration of the ten Southeast Asian countries develops rapidly, which is coupled by their increasing weight in the world trade. The dynamic economic and social development in the ASEAN region – and in parallel with this the growing demands and purchasing power - may encourage the Hungarian ventures in theory. However, there are still very few Hungarian entrepreneurs, who are ready to enter the market in the region and able in long run to operate there successfully. It is a well-known fact that the since the regime has changed in Hungary, foreign trade became strongly concentrated towards the EU members. The ASEAN countries – because of the geographic distance and by other reasons - definitely cannot mean an alternative of the EU market, however in a certain extent they can relieve this one-sided concentration and may provide additional opportunities for the Hungarian export of goods, and rather to the export of Hungarian services and know-how. The ratio of the ASEAN region within the entire Hungarian foreign trade turnover is small nowadays, furthermore – according to the statistical figures – this region is rather an import resource for Hungary than being an export market. This fact – just itself – is should not be considered as problem. When the amount of the import exceeds the amount of exports, that means that it is more worthwhile to do business with suppliers from there countries than with others. By and large all this is prevalent to the field of the agricultural trade as well: Hungary imports a range of commodities which cannot be produced by domestic farmers or in Europe (spices, tropical fruits, etc.). It is obvious that the ASEAN region cannot be the major market for the Hungarian agricultural export, not even in long run. However, there are still a lot of opportunities to enlarge the turnover of goods and services and enhance the co-operation in this geographic region. In the last chapter, the authors outlined an example in case of Vietnam – co-operation of joint public warehousing of agricultural commodities – which may be a good example for the promising potential opportunities. In contrast with the majority of the ASEAN countries, the Hungaro-Vietnamese political and economic relations had started much earlier than the regime was changed in Hungary. However, the potential advantages arose from this fact – the network of connections and the sympathy of Vietnamese professionals graduated in Hungary, the reputation and popularity of Hungarian agricultural products and technologies, the achievements of R&D in the field of agriculture – could not be utilized from Hungarian side. Vietnam, however still preserved its socialist political establishment, but in terms of its economic development strategy and economic policy has gradually been standing on the basis of market orientation. Vietnam, with its population of ninety million shows a rapid and successful development and it means good opportunities even for Hungarian entrepreneurs. It would be a mistake to leave these potentials unused. JEL Classification: F14, Q17, R11, N75